Odds & ends - Ignatow, Amy (Amulet Books, 2018)
While the Odds crew tries to manage their bizarre superpowers, several of their less-than-gifted classmates have become town celebrities thanks to their suspiciously good exam results, prompting Jay and Nick to investigate.